2020
DOI: 10.3389/fendo.2020.00330
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Implications in Idiopathic and Syndromic Obesity in Childhood: An Update

Abstract: Childhood obesity is a modern worldwide epidemic with significant burden for health. It is a chronic metabolic disorder associated with multiple cardiovascular risk factors such as dyslipidemia, hypertension, stroke, and insulin resistance. Many obese adolescents remain obese into adulthood, with increased morbidity and mortality. As childhood obesity is a risk factor for adult obesity, the childhood obesity-related disorders account for an increased risk of cardiovascular consequences in adults, in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Childhood obesity often translates to an increased prevalence of CV risk factors and, consequently, cardiac events in adulthood. 24 , 25 Four large studies among children who followed the participants into adulthood showed a positive correlation between high childhood BMI and various CV risk factors. Adults with obesity who were overweight/obese as children had an increased risk of T2D, HT, dyslipidemia, and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood obesity often translates to an increased prevalence of CV risk factors and, consequently, cardiac events in adulthood. 24 , 25 Four large studies among children who followed the participants into adulthood showed a positive correlation between high childhood BMI and various CV risk factors. Adults with obesity who were overweight/obese as children had an increased risk of T2D, HT, dyslipidemia, and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of these factors collectively amplifies the risk of cardiovascular disease (CVD) in adulthood [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) [3] has placed childhood obesity as a global epidemic, where there has been a greater increase in relation to malnutrition, more than 40 million children under 5 years old are overweight or obese, and over 60% of these children will become adults with overweight or obesity and will have lower life expectancy. Childhood obesity can be considered an indicator of the levels of health and quality of life of people, since bad habits in childhood, such as poor nutrition, can provide damage throughout the course of life [4]. In this sense, the nutritional state presents itself as an important variable for health, considering that eating habits, when a child, will influence their overall health in various stages of life, from childhood to the adult phase.…”
Section: Introductionmentioning
confidence: 99%